F FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI IBU TENTANG PEMBERIAN IMUNISASI DASAR PADA BAYI USIA 0-9 BULAN DI WILAYAH KERJA PUSKESMAS ALALAK SELATAN BANJARMASIN - Angga Irawan; Muhammad Hatta Subakti; Nurul Hidayah (LPPM Universitas Sari Mulia, 2021)
Abstract: in Indonesian, abstract length of 200-250 words (Arial 10). The abstract is written in one paragraph which consists of background, research objectives, concise method, main results including new facts, main conclusions and their meaning/suggestions from research results for scientific or practical development. Paragraph is a part that can stand alone if it is separated from the entire text, therefore the information included must be able to reflect what is discussed in the whole text. Avoid including information that is not in the script. Contains all the keywords to be indexed. Background: One of the efforts to control disease is through immunization. Low immunization coverage indicates low motivation in providing basic immunization. The factors that influence this motivation include knowledge, perception and family support. Knowing the factors related to mother's motivation about giving basic immunization to infants aged 0-9 months. Method: This study used an analytical survey with a cross sectional approach. The population was all mothers of infants aged 0-9 months in the working area of the Alalak Selatan Banjarmasin Health Center, totaling 711 people. The samples taken were 98 people with purposive sampling technique. Data were analyzed using the Spearman Rank test with a confidence level of 95%. Conclusion: There is a relationship between knowledge, perceptions and family support with mother's motivation regarding basic immunization for infants aged 0-9 months. Puskesmas should be able to improve communication media, information and education about basic immunization completely through posters or leaflets.